2000
DOI: 10.1021/bi0004192
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Mechanism for Free Cholesterol and Phospholipid Efflux from Human Vascular Cells to Apolipoprotein A-1

Abstract: Smooth muscle and endothelial cells in vivo are quiescent yet exposed to high levels of lipoprotein lipids. Phospholipid (PL) and free cholesterol (FC) efflux maintain homeostasis. Smooth muscle cells (SMC) expressed high levels of ABC-1 transporter mRNA, and glyburide-dependent PL and FC efflux to apolipoprotein A-1 (apo A-1), the major protein of high-density lipoprotein. FC efflux was inhibited by vanadate and okadaic acid, while PL efflux was not. Phosphatidylcholine was the major PL transferred by both ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
172
4
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(197 citation statements)
references
References 48 publications
(74 reference statements)
19
172
4
2
Order By: Relevance
“…Transfer of cellular cholesterol to apoA-I from peripheral tissues is a two-step process, with the initially bound phospholipids facilitating subsequent efflux of FC (4). Conformational transitions in apoA-I occur in a complex cellular environment that is seldom accessible for direct physical studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer of cellular cholesterol to apoA-I from peripheral tissues is a two-step process, with the initially bound phospholipids facilitating subsequent efflux of FC (4). Conformational transitions in apoA-I occur in a complex cellular environment that is seldom accessible for direct physical studies.…”
Section: Resultsmentioning
confidence: 99%
“…More than 30 years of sustained research (2) has gone into understanding the mechanism(s) of protection that apoA-I provides against heart disease. The protective action of apoA-I and HDL is attributed to their central role in reverse cholesterol transport (RCT); a process in which apoA-I acts as an acceptor for sequential transfers of phospholipids and free cholesterol (FC) from peripheral tissues and transports cholesterol to the liver and other tissues for excretion and steroidogenesis (3,4). Modulation of the RCT pathway presents significant potential for treatment of heart disease (5).…”
mentioning
confidence: 99%
“…5). LY-A and LY-A/CERT cells showed similar sensitivity to amphotericin B, which kills cells by binding to cholesterol in the plasma mem- brane, 3 suggesting that they contain similar number of cholesterol molecules in the plasma membrane. These results suggested that the plasma membrane was reorganized and more cholesterol existed in non-raft domains in LY-A cells when SM content was reduced.…”
Section: Cholesterol Available To Cold M␤cd Extraction Ismentioning
confidence: 98%
“…2, G and H). To further confirm that the cholesterol efflux function mediates apoE-induced A␤ degradation, we blocked the ABCA1 activity with glyburide (46,47). ABCA1 mediates cholesterol efflux onto apolipoproteins to form HDL particles, and blocking the FIGURE 2.…”
Section: Facilitation Of A␤ Degradation Is a Common Feature Of Hdlmentioning
confidence: 99%